Pengaruh Pendidikan Kesehatan Tentang Personal Hygiene Terhadap Pengetahuan Dan Sikap Siswa Di SDN Rembes 1 Dusun Watugimbal Kecamatan Beringin Kabupaten Semarang - Aulia, Farah Ichtyarinie; , Abi Muhlisin, SKM, M.Kep; , Kartinah A. Kep, S. Kep (2014)
Personal hygiene in children is an attempt to maintain cleanliness and hygiene in him to obtain physical health and aims to prevent the onset of disease. Personal hygiene may include the cleanliness of hair, eyes, ears, nose, mouth, nails, genital and appearance. The purpose of this study was to determine the effect of health education on personal hygiene to the knowledge and attitudes in SDN Rembes 1 Watugimbal Village Sub District Bringin Semarang Regency. This type of research is quantitative descriptive method using cross sectional approach. Sampling using total sampling obtained 48 respondents consisting of 17 people were in grade 3, 18 people in grade 4 and 13 students in grade 5. The results were collected using a questionnaire Guttman scale and Likert scale with quasi experiment research design with design research pre-test and post-test One Group Design. Results obtained in the post-test students' knowledge with a high percentage of total 79.2%, being 20.8%, and 0.0% lower and the results obtained from the post-test on the attitudes of students with a percentage of 100% of respondents included in both categories. In terms of gender, female students are the most respondents with a percentage of 52.1%. results of analysys statistics obtained value Paired T test with p value of 0,003 < 0,05. Judging from the large majority of respondents age was 9 years old and most respondents in terms of classes taken from grade 5 of 20 students (41.7%). The results showed that the knowledge and attitudes of the respondents about personal hygiene unchanged.